Analisa implementasi PSAK 24 Revisi 2013 dalam meningkatkan kepuasan karyawan pada PT. Agranet Multicitra Siberkom - Gita Muniardiningrum; Trinandari Prasetya Nugrahanti (Sekolah Pascasarjana Perbanas Jakarta, 2019)
This study aims to: a) Know and analyze the calculation of PSAK 24 Revision 2013 in the short-term employment benefits, Post-employment, other long-term employee benefits and severance pay; b) Know and analyze the implementation of PSAK 24 Revision 2013 in return for employee satisfaction at PT. AgranetMulticitraSiberkom.The approach used in this research is qualitative approach, while the research method using descriptive method. The research technique is interview and observation on HRD and Accounting Division of PT. AgranetMulticitraSiberkom in Jakarta. Keywords: PSAK 24 Revision 2013, Financial Accounting Standards, Employee Benefits, Employee Satisfaction.